(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The purpose of this research was to prepare and evaluate monolithic drug-in-adhesive type patches of Rasagiline Mesylate (RM) containing penetration enhancer and having seven day wear property. Preformulation studies like solubility in permeation enhancers, compatibility study, transmission study, uptake study and crystallization study of Rasagiline Mesylate in various pressure sensitive adhesive polymers were performed. Transdermal system was prepared by solvent casting method. The effects of various permeation enhancers (Propylene Glycol, Oleic Acid, Isopropyl Palmitate, and lauryl lactate) on the ex-vivo transcutaneous absorption of Rasagiline Mesylate through human cadaver skin were evaluated by modified Franz diffusion cell system. Ex-vivo transcutaneous absorption of prepared transdermal patch was performed using different concentration of Lauryl lactate (3%, 5%, and 7%). In-vitro Adhesion testing (Peel, tack shear etc.) was performed on different dry GSM (Grams per Square Meter) of patch like 80GSM, 100 GSM and 150 GSM. The final transdermal patches were tested for appearance, weight of matrix, thickness, % assay of drug content, in-vitro adhesion testing, cold flow study and ex-vivo skin permeation studies. Based on crystallization study and adhesion testing, Durotak-4098 (14% drug concentration) was selected as pressure sensitive adhesive. Patch containing Lauryl lactate showed highest cumulative permeation compared to other permeation enhancers. The patch containing 5% laurel lactate showed greater transdermal flux (2.36 µg/cm2 /hr). Patch with 150 dry GSM showing promising adhesion properties. Backing film Scotchpak 9723 and release liner Saint Gobain 8310 was selected based on transmission and uptake study of Rasagiline Mesylate. Stability study indicates that developed formulation remains stable. In conclusion, the present research confirms the practicability of developing Rasagiline Mesylate transdermal system.